Motivational role in the management of personnel management: theoretical aspect - G. S. Shelkoplyasova; A. L. Kobleva (Вестник Северо-Кавказского федерального университета, 2022)
The article offers a view on the role of motivational management in staff management system. The ability to motivate and stimulate staff is the major indicator of successful management in a company. We believe that professional competence and the skills in the staff will not yield a positive result unless there is the major thing - desire to work. Therefore each manager should first of all think about motivating the staff.